A ancestralidade como vereda para combater o racismo estrutural: uma análise literária e cultural da obra Ponciá Vicêncio, de Conceição Evaristo. - Gomes, Adrielly da Silva (2024)
Constantly, structural racism is seen as the beginning and end of the history of the Black population in Brazilian society, and this narrative permeates the social imagination as a single story. In light of this, this dissertation aimed to develop an understanding that the history of Afro-Brazilians goes beyond this harmful structure, which manifests itself in various facets, including structural racism. Through the analysis of the work Ponciá Vicêncio, an attempt was made to ascertain whether ancestry could be a fruitful path to combat racism. Additionally, the work sought to observe in the book the elements that refer to ancestry and that are present in the experience of many people, within and outside African-derived religions. The work Ponciá Vicêncio provided ample opportunity for the realization of personal and original reflections on issues related to enunciation and performance in linguistic-literary studies, as well as allowing for a new reflection on Conceição Evaristo's studies on escrevivência.